Long-Term Sinonasal Carriage of Staphylococcus aureus and Anti-Staphylococcal Humoral Immune Response in Patients with Chronic Rhinosinusitis - Ulrica Thunberg; Svante Hugosson; Ralf Ehricht; Stefan Monecke; Elke Müller; Yang Cao; Marc Stegger; Bo Söderquist (Microorganisms, 2021)
We investigated Staphylococcus aureus diversity, genetic factors, and humoral immune responses against antigens via genome analysis of S. aureus isolates from chronic rhinosinusitis (CRS) patients in a long-term follow-up. Of the 42 patients who provided S. aureus isolates and serum for a previous study, 34 could be included for follow-up after a decade. Clinical examinations were performed and bacterial samples were collected from the maxillary sinus and nares. S. aureus isolates were characterized by whole-genome sequencing, and specific anti-staphylococcal IgG in serum was determined using protein arrays. S. aureus was detected in the nares and/or maxillary sinus at both initial inclusion and follow-up in 15 of the 34 respondents (44%). Three of these (20%) had S. aureus isolates from the same genetic lineage as at inclusion. A low number of single-nucleotide polymorphisms (SNPs) were identified when comparing isolates from nares and maxillary sinus collected at the same time point. The overall change of antibody responses to staphylococcal antigens over time showed great variability, and no correlation was found between the presence of genes encoding antigens and the corresponding anti-staphylococcal IgG in serum; thus our findings did not support a role, in CRS, of the specific S. aureus antigens investigated.